2019
DOI: 10.1002/jcla.22834
|View full text |Cite
|
Sign up to set email alerts
|

Association of pro‐ and anti‐inflammatory cytokines in preeclampsia

Abstract: IntroductionThe pro‐ and anti‐inflammatory cytokines play crucial role in the development and functions of placenta. Any changes in these cytokines may be associated with many pregnancy‐related disorders like preeclampsia. Therefore, the present study is aimed to study the expression of pro‐inflammatory (TNF‐α, IL‐6) and anti‐inflammatory (IL‐4, IL‐10) cytokines in placenta and serum of preeclamptic pregnant women.Material and MethodsFor this study, a total of 194 cases of preeclamptic and control cases were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
122
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 35 publications
8
122
1
6
Order By: Relevance
“…Obesity-induced metabolic dysfunction and pregnancy complications share mechanistic similarities. Specifically, proinflammatory factors such as HMGB1 [112][113][114][115], TNF-α [116,117], and IL-1β [118][119][120] play critical roles in the inflammation underlying both obesity and preeclampsia. These key inflammatory mediators when upregulated in obesity [102] may potentiate aberrant maternal inflammation that in turn contribute to the development of pregnancy disorders [121].…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Obesity-induced metabolic dysfunction and pregnancy complications share mechanistic similarities. Specifically, proinflammatory factors such as HMGB1 [112][113][114][115], TNF-α [116,117], and IL-1β [118][119][120] play critical roles in the inflammation underlying both obesity and preeclampsia. These key inflammatory mediators when upregulated in obesity [102] may potentiate aberrant maternal inflammation that in turn contribute to the development of pregnancy disorders [121].…”
Section: Maternal Obesitymentioning
confidence: 99%
“…The shift in the balance of M2/M1 macrophages towards M1 is explained by high levels of pro-inflammatory cytokines and low levels of anti-inflammatory cytokines within the preeclamptic placenta [107,108]. In addition to the altered cytokine production, there is also a cellular axis in the process of polarization.…”
Section: Monocyte–macrophage System During Pregnancymentioning
confidence: 99%
“…Excessive TNF- α causes thrombosis and TNF- α can activate immunocompetent cells in the decidual stroma, induce immune-mediated destruction and immune rejection, hinder the maintenance of pregnancy and embryo implantation, disrupt the homeostasis of the maternal uterine environment, and cause spontaneous abortion [ 16 , 18 , 19 ]. IL-6, which is produced by extravillous trophoblasts and cytotrophoblasts, plays an important role in the normal placental development and pregnancy success by regulating placental cell migration and invasion and trophoblast differentiation and proliferation [ 20 , 21 ]. However, the role of IL-6 in ACA-positive spontaneous abortion is controversial, as Krause et al [ 22 ] showed that the serum IL-6 was increased in ACA-positive pregnant mice, while Karakantza et al [ 23 ] reported the opposite result.…”
Section: Discussionmentioning
confidence: 99%